(untitled) (Communications in Computational Physics, 2008)
This paper focuses on the numerical study of heat and moisture transfer in clothing assemblies, based on a multi-component and multiphase flow model which includes heat/moisture convection and conduction/diffusion as well as phase change. A splitting semi-implicit finite volume method is proposed for solving a set of nonlinear convection-diffusion-reaction equations, in which the calculation of liquid water content absorbed by fiber is decoupled from the rest of the computation. The method maintains the conservation of air, vapor and heat flux (energy). Four types of clothing assemblies are investigated and comparison with experimental measurements are also presented.